Anesthesia providers as stakeholders to adoption of pharmacogenomic information in perioperative care. Issue 3 (23rd September 2021) - Truong, Tien M.; Apfelbaum, Jeffrey L.; Schierer, Emily; Danahey, Keith; Borden, Brittany A.; Karrison, Theodore; Shahul, Sajid; Anitescu, Magdalena; Gerlach, Rebecca; Knoebel, Randall W.; Meltzer, David O.; Ratain, Mark J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Integration of pharmacogenomics into clinical care is being studied in multiple disciplines. We hypothesized that understanding attitudes and perceptions of anesthesiologists, critical care and pain medicine providers would uncover unique considerations for future implementation within perioperative care. Methods: A survey (multiple choice and Likert-scale) was administered to providers within our Department of Anesthesia and Critical Care prior to initiation of a department-wide prospective pharmacogenomics implementation program. The survey addressed knowledge, perceptions, experiences, resources and barriers. Results: Of 153 providers contacted, 149 (97%) completed the survey. Almost all providers (92%) said that genetic results influence drug therapy, and few (22%) were skeptical about the usefulness of pharmacogenomics. Despite this enthusiasm, 87% said their awareness about pharmacogenomic information is lacking. Feeling well-informed about pharmacogenomics was directly related to years in practice/experience: only 38% of trainees reported being well-informed, compared to 46% of those with 1–10 years of experience, and nearly two-thirds with 11+ years ( P < 0.05). Regarding barriers, providers reported uncertainty about availability of testing, turnaround time and whether testing is worth financial costs. Conclusions: Anesthesiology, critical care and pain medicine providers are optimistic about the potential clinical utility of pharmacogenomics, but are uncertain about practical aspects of testing and desire clear guidelines on the use of results. These findings may inform future institutional efforts toward greater integration of genomic results to improve medication-related outcomes.